Metadata–enhanced exploration of digital cultural collections. (11th April 2014) - Hampson, Cormac; Lawless, Séamus; Bailey, Eoin; Steiner, Christina M.; Hillemann, Eva–Catherine; Conlan, Owen
The increased digitisation of cultural collections and their availability on the World Wide Web has made access to these valuable documents much easier than ever before. However, despite the increased availability of access to cultural archives, curators still struggle to instigate and enhance engagement with these resources. The CULTURA project is actively addressing this issue through the development of a metadata–driven personalisation environment for exploring cultural collections and instigating collaborations. This paper discusses the state of the art in this area and the various innovative approaches used in the CULTURA project, with a special focus on how the underlying metadata helps to facilitate its semantically rich environment. An evaluation of the CULTURA project with students is detailed, highlighting its relevance for those without domain expertise. This is vital as the system needs to adapt and support a full spectrum of users, from professional researchers to interested members of the public.